2017
DOI: 10.5474/geologija.2017.018
|View full text |Cite
|
Sign up to set email alerts
|

REE-bearing minerals in Drava river sediments, Slovenia, and their potential origin

Abstract: Monazite and xenotime are major ore minerals for rare earth elements (REE), Y, and actinides, a powerful tool for radiometric dating and indicators of the geological genesis of the parent rock. In this contribution, we present results of microanalysis of monazite and xenotime mineral grains found in heavy mineral sand fraction from Drava river. Investigated grains of monazite(-Ce) were found to be exhibiting varying concentrations of Th, indicating mixed hydrothermal (or greenschist-amphibolite grade) and igne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The town of Maribor developed on the Drava River alluvial plain, which is represented by Quaternary glacio-fluvial and fluvial sediments, consisting mainly of metamorphic and igneous rock fragments (Mencin Gale et al, 2019;Mioč & Žnidarčič, 1989;Šoster et al, 2017;Trajanova, 2002;Žlebnik, 1982). The surroundings of the town are dominated by the hilly area of Slovenske Gorice, consisting of Miocene sedimentary rocks (mainly siliciclastic rocks), and by the Pohorje and Kozjak Mountains, consisting of a variety of metamorphic and igneous rocks (Hinterlechner Ravnik, 1971;Mioč, 1978;Mioč & Žnidarčič, 1989;Zupančič, 1994).…”
Section: Study Areamentioning
confidence: 99%
“…The town of Maribor developed on the Drava River alluvial plain, which is represented by Quaternary glacio-fluvial and fluvial sediments, consisting mainly of metamorphic and igneous rock fragments (Mencin Gale et al, 2019;Mioč & Žnidarčič, 1989;Šoster et al, 2017;Trajanova, 2002;Žlebnik, 1982). The surroundings of the town are dominated by the hilly area of Slovenske Gorice, consisting of Miocene sedimentary rocks (mainly siliciclastic rocks), and by the Pohorje and Kozjak Mountains, consisting of a variety of metamorphic and igneous rocks (Hinterlechner Ravnik, 1971;Mioč, 1978;Mioč & Žnidarčič, 1989;Zupančič, 1994).…”
Section: Study Areamentioning
confidence: 99%
“…joining Drava near Lienz, and Möll with its source near Heiligenblutt below Großglockner (3798 m a.s.l.) [27]. According to Bermanec et al [28] the region of Hoche Tauern is considered to be the source of gold found in fluvial sediments of river Drava from Maribor in Slovenia downstream.…”
Section: Study Areamentioning
confidence: 99%